Pemanfaatan Chatbot Berbasis Perangkat Pintar dengan Pendekatan Interaktif-Partisipatif untuk Pendampingan Kader Kesehatan: Narrative Literature Review - Achmad Solechan; Ellyzabeth Sukmawati; Kristina Maharani (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2026)
Community health workers play a vital role in community-based healthcare but often face challenges related to limited training, access to reliable information, and continuous supervision. This study aimed to examine the use of smart device–based chatbots with an interactive and participatory approach to support community health workers. A Narrative Literature Review was conducted on 30 Indonesian- and English-language articles published between 2019 and 2026. The findings indicate that chatbots function as educational resources, consultation tools, case simulation media, monitoring systems, and supervision support. Smartphone-based platforms, particularly WhatsApp, enhance accessibility because they are widely used by community health workers. Interactive features, including two-way communication, quizzes, simulations, and immediate feedback, improve users’ knowledge, skills, confidence, and work practices. Participatory development involving community health workers and health professionals increases system relevance and usability. However, implementation remains constrained by digital literacy, internet access, data privacy, information validity, and unequal device availability. Chatbots should therefore be implemented as complementary technologies supported by professional supervision, validated knowledge resources, and clear referral mechanisms to strengthen community-based health services.